Supply Chain Performance Measurement Framework for Construction Materials: Micro Meso Macro - Moh Nur Sholeh; Mochamad Agung Wibowo; Naniek Utami Handayani (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2020)
Productivity is a challenge in the construction industry, commonly initiated by fragmentation. In addition, some work levels have been identified, including the micro, meso, and macro. However, the construction supply chain is one of the possible solutions adopted to increase productivity. The purpose of this study, therefore, is to develop a framework for measuring supply chain construction performance at the micro, meso, and macro levels. These respective stages are tiered from the bottom to the top level as a supply chain management concept. Furthermore, a design for the supply chain performance measurement framework is created, followed by formulation with KPI, and the consequent application in the project. Therefore, performance is evaluated based on the construction materials, as a large resource. The results identified the supply chain performance at the micro-level as the basis for possible measures between contractor and supplier, using the SCOR. However, the emphasis was made on the strength of construction companies with large suppliers at the meso level. Meanwhile, the macro-level includes the accumulation of related measurements from micro as well as meso, and are consequently used to define the relationship between construction actors at the national level.